Economic institutional evolution and further needs for adjustments: Township Village Enterprises in China - Qiuxia Zhu; Stefanie Elbern (University of Bonn, Center for Development Research (ZEF), 2002)
Township Village Enterprises (TVEs) have essentially contributed to China's economic development and institutional transformation over the last twenty years. One of the explanations for the mechanism of TVEs' growth is the co-operative culture theory which claims that Chinese - compared with other nationalities - could better resolve free riding problems and work more efficiently under collective TVEs. In this paper, based on official documents, statistical data and results from important surveys, we analyze the historic development of property rights in TVEs. We have proved that the evolution of TVEs' property rights depended on the interaction between peasants and policy makers. In this interaction process peasants showed strong pursuit of private ownership and policy makers reacted with delay towards owner interests. Owing to the delay of political adjustments, peasants had to adopt various ownership forms for their enterprises - joint households, collective and shareholding cooperative - in order to struggle against a discriminating environment for private ownership. This institutional evolution is not a proof for the co-operative culture theory, but instead for the conventional theory of property rights because the long struggle of the peasants finally led to one clearly defined form of ownership private property rights. We have tested our hypothesis in view of the following process: In the collective economy under the commune system, policy-makers changed the size of owner units of TVEs from big (commune) to small (production brigade or production group) and back in accordance with the importance of TVEs to the national economy. In the individual economy after the reform of land use rights, the property rights of TVEs were forced to change step by step to private property rights under the pressure of farm households striving for private ownership. The peasants instrumentalized the various vaguely defined property rights in order to avoid political risks. Due to the principal agent problem, the collective-owned TVEs went down despite political and financial support. The financial viability of private TVEs however grew in spite of their competition with collective-owned TVEs and severe political and financial discrimination. With the evolution of property rights in TVEs, at present private enterprises dominate the non farm sector in China's rural areas. These structural changes require adjustments of China's financial policy: Formerly, formal financial institutions directed their support mainly towards collective enterprises, whereas private TVEs depended on informal capital sources. In order to meet private TVEs' financial demands, the rural financial market which officially is still dominated by formal financial institutions should be replaced with a financial market consisting of legally recognized multiform-intermediaries.
Keywords: 330; Institutional and Behavioral Economics; Ländliche Wirtschaft; Eigentumsrecht; Institutioneller Wandel; Privatwirtschaft; Ländliches Finanzsystem; China